A method for preparing modified starch material
Through ball milling treatment and pulse electric field-assisted toughening treatment, combined with covalent bond grafting modification and montmorillonite enhancement, the problem of poor mechanical properties and barrier properties after film formation of modified starch materials is solved, and higher mechanical properties and barrier properties are achieved, which are suitable for medical packaging materials.
Patent Information
- Application Number
- CN202411460567.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing modified starch materials have poor mechanical properties and barrier properties after film formation, making it difficult to meet the needs of medical packaging materials.
The crystal structure of the starch is changed by ball milling treatment, combined with pulsed electric field to assist in toughening treatment, and the isophorone diisocyanate, acrylic and cellulose nanocrystals are used as treatment agents to perform covalent bond graft modification, and finally montmorillonite is added as a reinforcement to improve mechanical properties and barrier properties.
The mechanical properties and barrier properties of modified starch materials are significantly improved, making them more suitable for medical packaging materials, with excellent film forming performance and use stability.
Smart Images

Figure CN119192859B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a method for preparing a modified starch material. Background Art
[0002] Starch is a natural polymer produced by green plants through photosynthesis. It is a polysaccharide composed of a single type of sugar unit, mainly composed of amylopectin and amylose. The common point between amylopectin and amylose is that they both have α-1,4 glycosidic bonds, while the difference between the two is that amylopectin has an α-1,6 glycosidic bond connected every 20 to 25 glucose units. Starch is a commonly used dressing in pharmaceutical manufacturing, such as as a carrier material, as a coating material or as a drug capsule wrapping material. The quality attributes of starch give the dressing functional characteristics. Since starch molecules are prone to form strong hydrogen bonds, they lack toughness, making it difficult to obtain a carrier material with significant mechanical properties.
[0003] In the prior art, there are also methods for improving the film-forming mechanical properties of starch by modifying starch. The modification methods generally include physical modification and chemical modification. Among them, physical modification mainly changes the properties of starch by the physical action of thermal field, force field and electric field on the original starch, such as microwave modification, ultrasonic modification, ball milling and extrusion. Chemical modification chemically reacts with the original starch by adding chemical reagents, thereby changing the molecular structure of starch and changing the properties of starch. However, the modified starch in the prior art cannot be optimized from a multi-dimensional perspective, especially when used as a medical packaging material, there are still problems of poor strength and poor barrier properties. For example, the Chinese invention patent publication number CN110372802A discloses a modification method for preparing citric acid starch ester using a subcritical extrusion device. The raw materials are mixed with citric acid and other additives by dry method, sealed and placed, and the finished product is obtained after subcritical extrusion, alcohol washing, drying, crushing and screening. The preparation process requires the use of a relatively high temperature, which will cause the degradation of starch and partial structural damage, and the strength cannot be improved. The modified starch is easy to break after film formation. Another example is the Chinese invention patent publication number CN109370474A, which discloses a dry method using radiation-microwave combination to prepare esterified potato starch, but the modified starch obtained by this method has poor toughening and barrier properties. Therefore, it is of positive significance to provide a starch modification scheme to improve its film-forming mechanical properties and barrier properties, making it more suitable for use as a medical material. Summary of the invention
[0004] Based on this, in order to solve the technical problems of poor uniformity of modified starch, poor mechanical properties after film formation and poor barrier properties in the prior art, the present invention provides a method for preparing a modified starch material, and the specific technical scheme is as follows:
[0005] A method for preparing a modified starch material, the method comprising the following steps:
[0006] Adding plant starch into a reactor, adding deionized water, and ball milling to obtain starch milk;
[0007] The starch milk is toughened under the condition of being lower than the initial gelatinization temperature of the plant starch, and then acetic anhydride is added to perform a first modification treatment. After completion, a treatment agent accounting for 10% to 15% of the mass of the plant starch is added to perform a second modification treatment, and the starch is washed to neutrality and subjected to centrifugal treatment to obtain modified starch;
[0008] The modified starch is mixed with the enhancer, an appropriate amount of deionized water is added, homogenized, bubbles are fully removed, film is cast, refrigerated and vacuum dried to obtain a modified starch material;
[0009] The treating agent is prepared by reacting isophorone diisocyanate, acrylic acid and cellulose nanocrystals at 120° C. to 125° C. for 1 h to 3 h.
[0010] Furthermore, the liquid volume ratio of the plant starch to the deionized water is (30-35):100.
[0011] Furthermore, the toughening treatment process needs to be assisted by a pulse electric field, and the conditions for the pulse electric field assistance are: an electric field strength of 20 v / m to 25 v / m, a frequency of 100 Hz to 120 Hz, and a time of 5 s to 30 s.
[0012] Furthermore, during the toughening treatment, a NaOH solution with a mass percentage concentration of 0.1% to 0.5% is added to adjust the starch emulsion, and the toughening treatment time is 30 minutes to 60 minutes.
[0013] Furthermore, the added amount of the acetic anhydride accounts for 12% to 15% of the mass of the plant starch.
[0014] Furthermore, the conditions of the first modification treatment are: temperature of 30°C to 45°C and time of 1h to 3h.
[0015] Furthermore, the mass ratio of isophorone diisocyanate, acrylic acid and cellulose nanocrystals is (1-7): (1-5): (1-2).
[0016] Furthermore, the conditions of the second modification treatment are: temperature of 55°C to 60°C and time of 2h to 3h.
[0017] Furthermore, the reinforcing agent is montmorillonite, and the added amount of the montmorillonite accounts for 0.1% to 0.3% of the mass of the modified starch.
[0018] Furthermore, the temperature of the cold storage treatment is 1°C to 5°C, and the time is 15h to 20h.
[0019] Compared with the prior art, the beneficial effects include:
[0020] 1. The present invention can mechanically change the crystal structure of plant starch through ball milling treatment, so that the hydroxyl content is reduced, which is helpful to promote water molecules to enter the amorphous area of starch particles, expand under the action of heat, and under the action of NaOH, the starch particles are concave inward and the shape becomes irregular. Combined with the assistance of pulse electric field, the rupture of cavitation bubbles formed during the toughening process can be accelerated, and the softening and toughening process of starch can be accelerated. The surface of the starch after toughening treatment is rough, the cracks and holes increase, the pores of the particles become larger, and the larger specific surface area can significantly improve the effects of the first modification treatment and the second modification treatment, so as to obtain modified starch with excellent quality.
[0021] 2. The treatment agent of the present invention is obtained by compounding isophorone diisocyanate, acrylic acid and cellulose nanocrystals, and is grafted with starch in a covalent bond manner, which helps to improve the structural stability and mechanical properties of the modified starch.
[0022] 3. The reinforcing agent added in the present invention can enter the structure of the modified starch, making the network structure of the starch denser and filling the gaps between the modified starch molecules, which helps to further improve the mechanical properties and barrier properties. In addition, through the block and grafting compounding of the modified starch, the modified starch can also enter the intercalation structure of the montmorillonite, increasing the storage stability and use stability at room temperature, and making the modified starch material have excellent film-forming properties, and the mechanical properties and barrier properties are both in line with the use of medical packaging materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention may be further understood from the following description taken in conjunction with the accompanying drawings, which are not necessarily drawn to scale, emphasis instead being placed on illustrating the principles of the embodiments.
[0024] Figure 1 This is an electron microscope magnified schematic diagram of cassava starch before and after toughening treatment in Example 1 of the present invention, wherein: Figure 1 a in the figure is an electron microscope magnified schematic diagram of cassava starch before toughening treatment in Example 1, Figure 1 b is an electron microscope magnified schematic diagram of cassava starch after toughening treatment in Example 1;
[0025] Figure 2 Schematic diagram of the electrolytic enlargement of corn starch before and after toughening treatment in Example 3 of the present invention, wherein: Figure 2 c is an electron microscope magnified schematic diagram of corn starch before toughening treatment in Example 3, Figure 2 d in the figure is an electron microscope magnified schematic diagram of corn starch after toughening treatment in Example 3;
[0026] Figure 3 The schematic diagram of the appearance of the cassava starch and modified starch materials after film formation in Example 1, wherein: Figure 3 Figure e in the figure is a schematic diagram of the appearance of cassava starch after film formation. Figure 3 f is a schematic diagram of the appearance of the modified starch material after film formation in Example 1;
[0027] Figure 4 Schematic diagram of the appearance of corn starch and modified materials after film formation in Example 3, wherein: Figure 4 Figure g is a schematic diagram of the appearance of corn starch after film formation. Figure 4 Figure h in the figure is a schematic diagram of the appearance of the modified starch material after film formation in Example 3. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] A method for preparing a modified starch material in one embodiment of the present invention comprises the following steps:
[0031] Adding plant starch into a reactor, adding deionized water, and ball milling to obtain starch milk;
[0032] The starch milk is toughened under the condition of being lower than the initial gelatinization temperature of the plant starch, and then acetic anhydride is added to perform a first modification treatment. After completion, a treatment agent accounting for 10% to 15% of the mass of the plant starch is added to perform a second modification treatment, and the starch is washed to neutrality and subjected to centrifugal treatment to obtain modified starch;
[0033] The modified starch is mixed with the enhancer, an appropriate amount of deionized water is added, homogenized, bubbles are fully removed, film is cast, refrigerated and vacuum dried to obtain a modified starch material;
[0034] The treating agent is prepared by reacting isophorone diisocyanate, acrylic acid and cellulose nanocrystals at 120° C. to 125° C. for 1 h to 3 h.
[0035] In one embodiment, the plant starch is at least one of corn starch, tapioca starch, wheat starch, pea starch, and potato starch.
[0036] In one embodiment, the liquid volume ratio of the plant starch to the deionized water is (30-35):100.
[0037] In one embodiment, the ball milling process is performed at a rotation speed of 500 r / min to 1000 r / min and a time of 10 min to 20 min.
[0038] In one of the embodiments, pulse electric field assistance is required during the toughening process, and the conditions for the pulse electric field assistance are: electric field intensity of 20v / m-25v / m, frequency of 100Hz-120Hz, and time of 5s-30s.
[0039] In one of the embodiments, during the toughening treatment, a NaOH solution with a concentration of 0.1% to 0.5% by mass is added to adjust the starch emulsion, and the toughening treatment time is 30 minutes to 60 minutes.
[0040] In one embodiment, the added amount of the acetic anhydride accounts for 12% to 15% of the mass of the plant starch.
[0041] In one embodiment, the conditions of the first modification treatment are: temperature of 30°C to 45°C and time of 1h to 3h.
[0042] In one of the embodiments, the mass ratio of isophorone diisocyanate, acrylic acid and cellulose nanocrystals is (1-7):(1-5):(1-2).
[0043] In one embodiment, the conditions of the second modification treatment are: temperature of 55°C to 60°C and time of 2h to 3h.
[0044] In one embodiment, the reinforcing agent is montmorillonite, and the added amount of the montmorillonite accounts for 0.1% to 0.3% of the mass of the modified starch.
[0045] In one embodiment, the homogenization treatment is carried out at a temperature of 30°C to 45°C, a pressure of 50MPa to 100MPa, and the homogenization is repeated several times.
[0046] In one embodiment, the refrigeration treatment is carried out at a temperature of 1°C to 5°C and for a time of 15h to 20h.
[0047] In one embodiment, the temperature of the vacuum drying process is 40°C to 50°C.
[0048] In one embodiment, the modified starch material is used as a drug packaging material or a drug capsule material.
[0049] In one embodiment, the modified starch material can be used as a raw material and compounded with other ingredients according to the actual performance of the drug packaging material, and then cast into a film through a cast film process to obtain a new drug packaging material.
[0050] The modified starch material obtained in the above scheme has excellent mechanical properties and barrier properties, can be used as a drug packaging material, and can impart excellent mechanical properties and barrier properties to the drug packaging material.
[0051] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0052] Embodiment 1:
[0053] A method for preparing a modified starch material, the method comprising the following steps:
[0054] According to the volume ratio of material to liquid of 35:100, cassava starch and deionized water were added into the reactor, and ball milled at a speed of 800 r / min for 15 min to obtain starch milk;
[0055] The initial gelatinization temperature of cassava starch was determined to be 66.1°C by DSC 200F3, and the starch emulsion was subjected to toughening treatment at 60°C for 45 minutes, and a NaOH solution with a mass percentage concentration of 0.3% was added to adjust the starch emulsion during the toughening treatment, and a pulse electric field was added during the toughening treatment, and the pulse electric field was assisted by the following conditions: the electric field strength was 20v / m, the frequency was 100Hz, and the time was 20s;
[0056] Then, acetic anhydride accounting for 12% of the mass of the cassava starch is added, and a first modification treatment is carried out at a temperature of 35°C for 2 hours. After completion, a treatment agent accounting for 12% of the mass of the cassava starch is added, and a second modification treatment is carried out at a temperature of 55°C for 2 hours, washed to neutrality, and centrifuged to obtain modified starch; the treatment agent in this embodiment is obtained by mixing isophorone diisocyanate, acrylic acid and cellulose nanocrystals in a mass ratio of 6:3:1, and reacting at 120°C for 2 hours;
[0057] The modified starch was mixed with montmorillonite accounting for 0.3% of the mass of the modified starch, and an appropriate amount of deionized water was added. After homogenization treatment for 3 times at a temperature of 30° C. and a pressure of 50 MPa, bubbles were fully discharged, and the film was cast. The modified starch material was obtained after refrigeration treatment at a temperature of 1° C. for 15 hours and vacuum drying at 45° C.
[0058] Embodiment 2:
[0059] A method for preparing a modified starch material, the method comprising the following steps:
[0060] According to the material-liquid volume ratio of 35:100, cassava starch and deionized water were added into the reactor, and ball milled at a speed of 1000 r / min for 15 min to obtain starch milk;
[0061] The initial gelatinization temperature of cassava starch was determined to be 66.1°C by DSC 200F3, and the starch emulsion was subjected to toughening treatment at 60°C for 50 minutes, and a NaOH solution with a mass percentage concentration of 0.5% was added to adjust the starch emulsion during the toughening treatment, and a pulse electric field was added during the toughening treatment, and the pulse electric field was assisted by the following conditions: the electric field strength was 20v / m, the frequency was 120Hz, and the time was 18s;
[0062] Then, acetic anhydride accounting for 15% of the mass of the cassava starch is added, and a first modification treatment is performed at a temperature of 40°C for 2 hours. After completion, a treatment agent accounting for 15% of the mass of the plant starch is added, and a second modification treatment is performed at a temperature of 60°C for 2 hours, and the starch is washed to neutrality and centrifuged to obtain modified starch. The treatment agent in this embodiment is obtained by mixing isophorone diisocyanate, acrylic acid and cellulose nanocrystals in a mass ratio of 7:2:1, and reacting at 125°C for 2 hours.
[0063] The modified starch was mixed with montmorillonite accounting for 0.3% of the mass of the modified starch, and an appropriate amount of deionized water was added. After homogenization treatment for 3 times at a temperature of 30° C. and a pressure of 50 MPa, bubbles were fully discharged, and the film was cast. The film was refrigerated at a temperature of 1° C. for 15 hours, and vacuum dried at 50° C. to obtain a modified starch material.
[0064] Embodiment 3:
[0065] A method for preparing a modified starch material, the method comprising the following steps:
[0066] Corn starch and deionized water were added into a reactor at a material-liquid volume ratio of 35:100, and ball-milled at a speed of 1000 r / min for 20 min to obtain starch emulsion;
[0067] The initial gelatinization temperature of corn starch was determined to be 69.5°C by DSC 200F3, and the starch emulsion was subjected to toughening treatment at 60°C for 50 minutes, and a NaOH solution with a mass percentage concentration of 0.2% was added to adjust the starch emulsion during the toughening treatment, and a pulse electric field was added during the toughening treatment, and the pulse electric field was assisted by the following conditions: the electric field strength was 25v / m, the frequency was 100Hz, and the time was 15s;
[0068] Then, acetic anhydride accounting for 12% of the mass of the corn starch is added, and a first modification treatment is carried out at a temperature of 45°C for 3 hours. After completion, a treatment agent accounting for 12% of the mass of the corn starch is added, and a second modification treatment is carried out at a temperature of 55°C for 2 hours. The corn starch is washed to neutrality and centrifuged to obtain modified starch. The treatment agent in this embodiment is obtained by mixing isophorone diisocyanate, acrylic acid and cellulose nanocrystals in a mass ratio of 5:4:1 and reacting at 125°C for 2 hours.
[0069] The modified starch was mixed with montmorillonite accounting for 0.3% of the mass of the modified starch, and an appropriate amount of deionized water was added. After homogenization treatment for 3 times at a temperature of 30° C. and a pressure of 50 MPa, bubbles were fully discharged, and the film was cast. The modified starch material was obtained after refrigeration treatment at a temperature of 1° C. for 15 hours and vacuum drying at 45° C.
[0070] Embodiment 4:
[0071] A method for preparing a modified starch material, the method comprising the following steps:
[0072] Corn starch and deionized water were added into a reactor at a material-liquid volume ratio of 35:100, and ball-milled at a speed of 1000 r / min for 20 min to obtain starch emulsion;
[0073] The initial gelatinization temperature of corn starch was determined to be 69.5°C by DSC 200F3, and the starch emulsion was subjected to toughening treatment at 60°C for 60 minutes, and a NaOH solution with a mass percentage concentration of 0.3% was added to adjust the starch emulsion during the toughening treatment, and a pulse electric field was added during the toughening treatment, and the pulse electric field was assisted by the following conditions: the electric field strength was 25v / m, the frequency was 110Hz, and the time was 10s;
[0074] Then, 15% of acetic anhydride by weight of the corn starch is added, and a first modification treatment is performed at a temperature of 45° C. for 3 hours. After completion, a treatment agent by weight of 15% of the corn starch is added, and a second modification treatment is performed at a temperature of 60° C. for 2 hours. The corn starch is washed to neutrality and centrifuged to obtain modified starch. The treatment agent in this embodiment is obtained by mixing isophorone diisocyanate, acrylic acid and cellulose nanocrystals in a mass ratio of 7:2:1 and reacting at 125° C. for 2 hours.
[0075] The modified starch was mixed with montmorillonite accounting for 0.3% of the mass of the modified starch, and an appropriate amount of deionized water was added. After homogenization treatment for 3 times at a temperature of 30° C. and a pressure of 50 MPa, bubbles were fully discharged, and the film was cast. The modified starch material was obtained after refrigeration treatment at a temperature of 1° C. for 15 hours and vacuum drying at 45° C.
[0076] Comparative Example 1:
[0077] The difference between Comparative Example 1 and Example 4 is that Comparative Example 1 is not toughened, and the rest is the same as Example 4.
[0078] Comparative Example 2:
[0079] The difference between Comparative Example 2 and Example 4 is that the toughening treatment in Comparative Example 2 is not assisted by a pulse electric field, and the rest is the same as Example 4.
[0080] Comparative Example 3:
[0081] The difference between Comparative Example 3 and Example 4 is that the pulse electric field assisting conditions in Comparative Example 3 are: electric field intensity of 10 v / m, frequency of 50 Hz, and time of 60 s. The rest are the same as Example 4.
[0082] Comparative Example 4:
[0083] The difference between Comparative Example 4 and Example 4 is that Comparative Example 4 does not undergo the first modification treatment, and the rest is the same as Example 4.
[0084] Comparative Example 5:
[0085] The difference between Comparative Example 5 and Example 4 is that Comparative Example 5 does not undergo the second modification treatment, and the rest is the same as Example 4.
[0086] Comparative Example 6:
[0087] The difference between Comparative Example 6 and Example 4 is that no cellulose nanocrystals are added to the treatment agent in Comparative Example 6, and the rest is the same as Example 4.
[0088] Comparative Example 7:
[0089] The difference between Comparative Example 7 and Example 4 is that the treatment agent in Comparative Example 7 is replaced by amylase, and the rest is the same as Example 4.
[0090] Comparative Example 8:
[0091] The difference between Comparative Example 8 and Example 4 is that the treatment agent in Comparative Example 8 is obtained by reacting isophorone diisocyanate, acrylic acid and cellulose nanocrystals in a mass ratio of 1:8:5 at 120°C for 2h, and the rest is the same as Example 4.
[0092] Comparative Example 9:
[0093] The difference between Comparative Example 9 and Example 4 is that no montmorillonite (reinforcer) is added in Comparative Example 9, and the rest is the same as Example 4.
[0094] Comparative Example 10:
[0095] The difference between Comparative Example 10 and Example 4 is that the added amount of montmorillonite (reinforcing agent) in Comparative Example 10 accounts for 5% of the mass of the modified starch, and the rest is the same as Example 4.
[0096] 1. The particle morphology of the modified starch material samples of Examples 1 to 4 of the present application during the preparation process was characterized by electron microscopy magnification. The results are shown in Table 1 below.
[0097] Table 1: Particle morphology
[0098]
[0099] In addition, combined Figure 1 to Figure 4 , Figure 1 This is an electron microscope magnified schematic diagram of cassava starch before and after toughening treatment in Example 1 of the present invention, wherein: Figure 1 a in the figure is an electron microscope magnified schematic diagram of cassava starch before toughening treatment in Example 1, Figure 1 b is an electron microscope magnified schematic diagram of cassava starch after toughening treatment in Example 1; Figure 1 It can be seen that the surface roughness of the cassava starch after toughening treatment increases and the number of cracks increases. Example 2 is similar to Example 1 and will not be described in detail here.
[0100] Figure 2 Schematic diagram of the electrolytic enlargement of corn starch before and after toughening treatment in Example 3 of the present invention, wherein: Figure 2 c is an electron microscope magnified schematic diagram of corn starch before toughening treatment in Example 3, Figure 2 d in the figure is an electron microscope magnified schematic diagram of corn starch after toughening treatment in Example 3; Figure 2 It can also be seen that the surface roughness of corn starch increases and the cracks increase after toughening treatment.
[0101] Embodiment 4 is similar to Embodiment 3 and will not be described again here.
[0102] Figure 3 The schematic diagram of the appearance of the cassava starch and modified starch materials after film formation in Example 1, wherein: Figure 3 Figure e in the figure is a schematic diagram of the appearance of cassava starch after film formation. Figure 3 f in the figure is a schematic diagram of the appearance of the modified starch material after film formation in Example 1; Figure 3 It can be seen that after the cassava starch is film-formed, the surface of the film is distributed with particles of different sizes, and the surface is not smooth enough, while after the modified starch material is film-formed, the particles are reduced and the surface is smooth, which is more conducive to its application in drug packaging materials. The film-forming performance of the modified starch material in Example 2 is similar to that in Example 1, and will not be repeated here.
[0103] Figure 4 Schematic diagram of the appearance of corn starch and modified materials after film formation in Example 3, wherein: Figure 4 Figure g is a schematic diagram of the appearance of corn starch after film formation. Figure 4 Figure h in the figure is a schematic diagram of the appearance of the modified starch material after film formation in Example 3. Figure 4 It can be seen that after the corn starch is formed into a film, there are many protrusions and it is not flat. After the modified starch material in Example 3 is formed into a film, the particles are broken, the continuous phase is more obvious, the film is smoother, and it is more suitable for use as a drug packaging material. The film-forming performance of the modified starch material in Example 4 is similar to that of Example 3, and will not be repeated here.
[0104] 2. The water vapor transmission rate, tensile strength and elongation at break of the modified starch material samples prepared in Test Examples 1 to 4 and the modified starch material comparison samples prepared in Comparative Examples 1 to 10 were tested. The performance characterization results are shown in Table 2 below.
[0105] Table 2: Performance characterization results
[0106]
[0107]
[0108] From the data analysis of Table 2, it can be seen that after the optimization of ingredients and processes, the present application can obtain modified starch materials with excellent barrier properties and mechanical properties. The difference between Comparative Examples 1 to 3 and Example 4 is that the toughening treatment processes of Comparative Examples 1 to 3 are different, but it can be seen that compared with Example 4, the barrier properties and mechanical properties are significantly reduced, indicating that the toughening treatment process has a promoting effect on the modification of starch. The difference between Comparative Examples 4 and Comparative Examples 5 and Example 4 is that Comparative Example 4 adopts a composite modification method, and the barrier properties and mechanical properties of the modified starch material obtained are better. The treatment agent in Comparative Examples 6 to 8 is different from that in Example 4. The results show that the barrier properties and mechanical properties of the modified starch material obtained are worse than those in Example 4, indicating that the use of the treatment agent of the present application also has a synergistic effect, and the selection of the treatment agent of the present application can promote the acquisition of materials with better performance. The addition of montmorillonite in Comparative Examples 9 and Comparative Examples 10 helps to improve the mechanical properties and barrier properties, but the addition of montmorillonite is too high, which will affect the elongation at break. Therefore, the present application has a preferred montmorillonite addition amount to make it more usable.
[0109] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0110] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a modified starch material, characterized in that: The preparation method comprises the following steps: Adding plant starch into a reactor, adding deionized water, and ball milling to obtain starch milk; The starch milk is toughened under the condition of being lower than the initial gelatinization temperature of the plant starch, and then acetic anhydride is added to perform a first modification treatment. After completion, a treatment agent accounting for 10% to 15% of the mass of the plant starch is added to perform a second modification treatment, and the starch is washed to neutrality and subjected to centrifugal treatment to obtain modified starch; The modified starch and the enhancer are mixed, an appropriate amount of deionized water is added, homogenization is performed, bubbles are fully removed, film is cast, refrigeration is performed, and vacuum drying is performed to obtain a modified starch material; The treating agent is prepared by reacting isophorone diisocyanate, acrylic acid and cellulose nanocrystals at 120° C. to 125° C. for 1 h to 3 h.
2. The preparation method according to claim 1, characterized in that: The liquid volume ratio of the plant starch to the deionized water is (30-35):
100.
3. The preparation method according to claim 1, characterized in that: The toughening treatment process needs to be supplemented with a pulse electric field, and the conditions for the pulse electric field supplement are: an electric field strength of 20 v / m to 25 v / m, a frequency of 100 Hz to 120 Hz, and a time of 5 s to 30 s.
4. The preparation method according to claim 3, characterized in that: During the toughening treatment, a NaOH solution with a mass percentage concentration of 0.1% to 0.5% is added to adjust the starch emulsion, and the toughening treatment time is 30 minutes to 60 minutes.
5. The preparation method according to claim 1, characterized in that: The added amount of the acetic anhydride accounts for 12% to 15% of the mass of the plant starch.
6. The preparation method according to claim 5, characterized in that: The conditions of the first modification treatment are: temperature of 30°C to 45°C and time of 1h to 3h.
7. The preparation method according to claim 1, characterized in that: The mass ratio of isophorone diisocyanate, acrylic acid and cellulose nanocrystals is (1-7): (1-5): (1-2).
8. The preparation method according to claim 7, characterized in that: The conditions of the second modification treatment are: temperature of 55°C to 60°C and time of 2h to 3h.
9. The preparation method according to claim 1, characterized in that: The reinforcing agent is montmorillonite, and the added amount of the montmorillonite accounts for 0.1% to 0.3% of the mass of the modified starch.
10. The preparation method according to claim 1, characterized in that: The temperature of the cold storage treatment is 1℃~5℃, and the time is 15h~20h.
Citation Information
Patent Citations
Method for preparing corrugated-paper adhesive by using irradiation-microwave to esterify potato starch
CN109370474A
Starch citrate and preparation method thereof
CN110372802A
Granulum starch with functions of nutrition enrichment and fat simulation and preparation method thereof
CN101880333A
Modified nanocellulose reinforced thermoplastic starch food packaging film preparation method
CN109354722A